Effect of Sensor and Based NPK on the Growth of Pakcoy (Brassica rapa L.) Cultivation Hydroponic - Sania, Hani; Fevria, Resti; Vauzia, Vauzia; Razak, Abdul; Yulkifli, Yulkifli; Mutiar, Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
In hydroponic cultivation, the effectiveness of nutrient distribution is crucial in ensuring optimal plant growth. This research aims to compare the efficiency of nutrient solution delivery using an Internet of Things (IoT)-based NPK sensor with the conventional manual method on the growth of pakcoy (Brassica rapa L.). The study was conducted using a Completely Randomized Design (CRD) with two treatment groups: one utilizing IoT-based NPK sensors and the other without sensors. Each treatment was repeated twice, with nine plant samples per repetition. The observed growth parameters included plant height, number of leaves, leaf area, fresh weight, and dry weight at six weeks after planting. The findings revealed that the implementation of IoT-based NPK sensors significantly enhanced the growth of pakcoy plants compared to the manual method. This was evidenced by a notable increase in plant height, leaf area, and fresh weight (p < 0.05). In conclusion, the application of IoT technology improves the efficiency and effectiveness of nutrient distribution in hydroponic systems, positively impacting plant growth. The scientific significance of this research suggests that integrating IoT-based technology into hydroponic farming can serve as an innovative approach to enhancing plant productivity in a precise and sustainable manner.